Series Type Vertical Subsurface Flow Constructed Wetlands for Dairy Farm Wastewater Treatment - Julius Cezar A. Galve; Marloe Baclayon Sundo; Donny Rey D. Camus; Victor Mikael N. De Padua; Richard Dean F. Morales (Salehan Institute of Higher Education, 2021)
Agricultural and livestock farms are the major sources of freshwater pollution in rural areas in the Philippines. Small and unregulated dairy farms operate without appropriate wastewater treatment before discharge because it is too expensive to do so. With this scenario, the emergence of the need for a sustainable and cheaper alternative for wastewater treatment gave rise to the research and development studies of the efficiency of constructed wetlands. The study aims to analyze the treatment efficiency of series type vertical subsurface flow constructed wetlands planted with Napier Grass (Pennisetum Purpureum Schumach) on University of the Philippines Los Baños (UPLB) Dairy Farm wastewater with a focus on fecal coliform concentration, electric conductivity, total dissolved solids content, nitrite and nitrate concentration and pH level. The study showed that after treatment using the vertical subsurface flow constructed wetlands, all the parameters except the fecal coliform concentration were below the standard limits set by the Department of Agriculture with average removal efficiencies of 12.94% on Electric Conductivity (EC), 12.86% on Total Dissolved Solids (TDS), 216.44% on Nitrite (NO2-N), -125.64% on Nitrate (NO3-N), and -25.64% on Fecal Coliforms (FC). With the results of the analysis, a design of series type vertical subsurface flow constructed wetland for dairy farm wastewater treatment is suggested. Doi: 10.28991/cej-2021-03091654 Full Text: PDF